Ionospheric Regions Producing Anomalous GNSS Radio Occultation Results - Norman, R.; Carter, B. A.; Healy, S. B.; Culverwell, I. D.; Von Engeln, A.; Le Marshall, J.; Younger, J. P.; Cate, A.; Zhang, K. (IEEE transactions on geoscience and remote sensing, 2018)
Anomalous GPS radio occultation (RO) events are characterised as those with L1 bending angle greater than their corresponding L2 bending angle. An investigation by EUMETSAT and the United Kingdom Meteorological Office revealed there are regions in the earth's atmosphere where at times up to 60% of Global Navigation Satellite System Receiver for Atmospheric Sounding RO events, at the Tangent Point height of 50 km, exhibited anomalous bending angle results. The exact source of these anomalous RO events has been unclear to the RO data user community, i.e., data processing artifact or atmospheric phenomenon. In this paper, the regions of increased occurrence of anomalous RO have been identified to be the mid-latitude ionospheric trough, ionospheric polar hole, and poleward edges of the equatorial anomaly. They are more frequent at nighttime and in the southern hemisphere winter months. This is when the plasma density in these regions is depleted. However, within these regions, there are ionospheric features of increased electron density gradients such as at the walls of the mid-latitude ionospheric trough. 3-D numerical ray tracing simulations of GPS RO are presented, showing that these increased electron density features in a weakly ionized ionosphere can produce the anomalous bending angle results.